Penguatan Literasi Keuangan dan Transformasi Pengelolaan KP-SPAMS Tirta Sari untuk Layanan Air Bersih Berkelanjutan - Darmayanti, Irma; Asriandhini, Bunga; Hermanto, Nandang; Herlambang, Ananda Putra; Putranto, Aldrian Firmansyah (Penerbit Widina, Widina Media Utama, 2025)
The availability of clean water is a fundamental community need, but ineffective management often hinders the sustainability of services. KP-SPAMS